SYNTHESIS OF SILVER NANOPARTICLES USING BIOREDUCTORS: MINI REVIEW - Indriani, Isah Waliah; Hindryawati, Noor; Hiyahara, Irfan Ashari (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Synthesis of silver nanoparticles can be carried out using bioreductors which are natural reducing agents from natural materials containing antioxidant compounds or polyols which can reduce silver due to the nucleophilic nature of phenolic compounds in plant secondary metabolites. The use of bioreductors in the manufacture of nanoparticles can reduce the adverse effects and hazardous waste generated due to reduced adsorption of the toxic properties of the solvent used. The content of organic compounds in bioreductors can be utilized, for example secondary metabolites such as terpenoids, flavonoids and tannins which act as antioxidants and capping agents, where Ag+ ions in AgNO3 can be reduced into silver nanoparticles, so bioreductors can replace the role of synthetic reducing agents. Based on the literature used, several plants whose extracts can be used as bioreductors, namely gambier, gotu kola leaves, water hyacinth leaves, bilimbi leaves, cempedak bark and bay leaves using variations in the concentration and composition of the AgNO3 solution. The results of silver nanoparticles were synthesized using bioreductors, namely various nano-sized particles and based on UV-Vis spectrophotometry data, silver nanoparticles appeared at wavelengths between 410 - 450 nm. Keywords: Secondary metabolites, Bioreductors, Silver Nanoparticles